Homonegative Victimization and Perceived Stress among Adolescent Sexual Minority Males: The Attenuating Role of Peer and Family Support. Issue 4 (2nd October 2022) - Gordián-Arroyo, Alvin; Schnall, Rebecca; Garofalo, Robert; Kuhns, Lisa M.; Pearson, Cynthia; Bruce, Josh; Batey, D. Scott; Radix, Asa; Belkind, Uri; Hirshfield, Sabina; Hidalgo, Marco A.
Abstract: Purpose : Research suggests social support may protect sexual minorities from the harmful effects of victimization that undermine mental and sexual health wellness; however, this relationship has been underexplored among a diverse youth population. We examined the association between lifetime homonegative victimization, perceived stress in the last month, and resilience factors among a diverse sample of adolescent sexual minority males. Methods : Data were collected between June 2018 and April 2020 as part of the MyPEEPS Mobile study, a multi-site randomized controlled trial evaluating the effectiveness of a mobile behavioral HIV prevention intervention for adolescents living in the U.S. We analyzed baseline survey data from 542 sexual minority males, aged 13–18 years. We used bivariate analyses to examine relationships among variables and multivariable linear regression models to determine if resilience factors attenuated the association between homonegative victimization and perceived stress. Results : Perceived stress was positively associated with younger age, internalized homophobia, experiencing verbal victimization, threats of being outed, and threats of physical violence. Relying on online friends for support and having good family relations both attenuated the relationship between verbal victimization and perceived stress. However, neither of these resilience factors significantly weakened the associations between perceived stress, threats of physical violence, and being outed. Conclusion : Resilience factors, including peer and family support, may play an attenuating role in the relationship between homonegative victimization and perceived stress among adolescent sexual minority males. ClinicalTrials.gov Identifier: NCT03167606